2019
DOI: 10.4085/1062-6050-260-17
|View full text |Cite
|
Sign up to set email alerts
|

Lesbian, Gay, Bisexual, Transgender, and Queer Patients: Collegiate Athletic Trainers' Perceptions

Abstract: Context Research suggests that patients who identify as lesbian, gay, bisexual, transgender, or queer (LGBTQ) are at risk for certain conditions and denied equal access to health care in physician offices compared with their heterosexual counterparts. However, little evidence exists regarding the treatment of LGBTQ student-athlete patients in the athletic training clinic and the role the athletic trainer (AT) plays in these health care experiences. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 21 publications
(31 reference statements)
1
25
0
Order By: Relevance
“…Specifically, in the collegiate and university setting, ATs can ensure quality care for transgender patients free of discrimination, with a focus on preventing injuries, illnesses, and conditions common to the transgender community. Previous authors 14,15 identified that health care professionals had a generally positive view of treating transgender patients but also that they felt inadequately educated and trained to do so. In addition, ATs must comply with the Board of Certification Standards of Professional Practice, which state one must ''render quality patient care regardless of the patient's age, gender, race, religion, disability, sexual orientation, or any characteristic protected by law.''…”
Section: O N L I N E F I R S Tmentioning
confidence: 99%
“…Specifically, in the collegiate and university setting, ATs can ensure quality care for transgender patients free of discrimination, with a focus on preventing injuries, illnesses, and conditions common to the transgender community. Previous authors 14,15 identified that health care professionals had a generally positive view of treating transgender patients but also that they felt inadequately educated and trained to do so. In addition, ATs must comply with the Board of Certification Standards of Professional Practice, which state one must ''render quality patient care regardless of the patient's age, gender, race, religion, disability, sexual orientation, or any characteristic protected by law.''…”
Section: O N L I N E F I R S Tmentioning
confidence: 99%
“…A common suggestion from participants was to increase the level of education ATs receive about transgender topics. Nye et al 19 observed that collegiate ATs desired more education and information on caring for transgender patients. In health care professions other than athletic training, researchers proposed that including LGBT education as part of professional curricula may have positive results.…”
Section: Suggestions For Addressing Barriersmentioning
confidence: 99%
“…At this point, the growing body of literature in athletic training related to lesbian, gay, bisexual, and transgender (LGBT) 2 patients has mostly considered the LGBT community as a whole and primarily examined ATs' perceptions of those patients. 19 No known literature exists regarding transgender patients' experiences with ATs. Athletic trainers treat patients from a variety of backgrounds in all settings, including athletics.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, patients who are of racial or ethnic minorities, such as primarily those that are BIPOC, have also experienced unconscious biases in medical care that lead to healthcare inequities. 1 Studies on athletic trainers' perceptions of lesbian, gay, and bisexual (LGB) patients 4 and LGBTQ+ patients 5 have shown that respondents overall had positive attitudes toward LGBTQ+ patients, however, this was largely dependent on clinicians being female and/or having a close friend or relative that identified as LBG or LGBTQ+. 4,5 To our knowledge, there are no published studies specific to the healthcare provided to BIPOC patients by athletic trainers.…”
Section: Introductionmentioning
confidence: 99%